2006
DOI: 10.1128/aem.72.5.3673-3677.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Quaternary Ammonium Silane Coatings on Mixed Fungal and Bacterial Biofilms on Tracheoesophageal Shunt Prostheses

Abstract: Two quaternary ammonium silanes (QAS) were used to coat silicone rubber tracheoesophageal shunt prostheses, yielding a positively charged surface. One QAS coating [(trimethoxysilyl)-propyldimethyloctadecylammonium chloride] was applied through chemical bonding, while the other coating, Biocidal ZF, was sprayed onto the silicone rubber surface. The sprayed coating lost its stability within an hour, while the chemically bonded coating appeared stable. Upon incubation in an artificial throat model, allowing simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 19 publications
1
74
0
1
Order By: Relevance
“…in biofilms formed at human chronic skin wounds [23]. FISH was also employed by Oosterhof et al to study mixed fungal and bacterial biofilms on tracheoesophageal shunt prostheses [24]. Not only in identification of microbial species, FISH based methods can also be used to estimate the physiological states of microbial cells.…”
Section: Methods For Study Of Multiple-species Biofilmsmentioning
confidence: 99%
“…in biofilms formed at human chronic skin wounds [23]. FISH was also employed by Oosterhof et al to study mixed fungal and bacterial biofilms on tracheoesophageal shunt prostheses [24]. Not only in identification of microbial species, FISH based methods can also be used to estimate the physiological states of microbial cells.…”
Section: Methods For Study Of Multiple-species Biofilmsmentioning
confidence: 99%
“…When used alone SYTO 9 labels both live and dead bacteria green, in contrast propidium iodide penetrates those cells with compromised cell membranes. The staining method has been used extensively as a viability indicator [33][34][35][36][37][38][39][40]. The stain mixture ratio used in the majority of experiments was 75 : 25, SYTO 9: propidium iodide rather than the recommended 1 : 1 ratio, this was due to the red fluorescence being too prominent.…”
Section: In Situ Viability Staining and Imagingmentioning
confidence: 99%
“…Positively charged surfaces are strongly adhesive to the negatively charged bacteria; however, the positive charge inhibited biofilm progression from the initial adhesion stage toward the growth stage since immobilized QAS molecules interact with the cell membranes of adhering bacteria, presumably causing membrane leakage and cell death. Oosterhof et al (2006) demonstrated that QAS also reduces the number of viable bacteria and yeasts in mixed biofilms. Upon incubation in an artificial throat model, allowing simultaneous adhesion and growth of yeast and bacteria, all coated prostheses showed significant reductions in the numbers of viable yeast and bacteria compared with those for silicone rubber controls, as confirmed using confocal laser scanning microscopy after live/dead staining of the biofilms.…”
Section: Metal Coating Techniques Arweiler-harbeck Et Al (2001)mentioning
confidence: 99%